PENERAPAN LEAN SIX SIGMA DI PERUSAHAAN FARMASI PADA PROSES PENGEMAS PRODUK BLISTER - Ongan, Freddy Bano; Kosasih, Wilson; Kristina, Helena Juliana (Universitas Tarumanagara, 2024)
Pharmaceutical Companies are manufacturing industries operating in the pharmaceutical sector where these companies produce solid, semi-solid and liquid product extractions. In the production process in the packaging section in dense areas as the object in this research, it is not uncommon to experience waste in the form of product defects such as dirty blisters, ciplongs, and so on, as well as non-value added activities. To solve this problem, a lean six sigma approach was carried out through the DMAIC stages. This research aims to find out the types of waste, find out the main causes of product defects, find out the DPMO value and sigma level, and provide solutions in the form of suggestions to overcome existing problems to Pharmaceutical Companies. Through the definition stage, it is known that the object of this research is product The data collection method used is through observation, interviews and questionnaires. Based on the known measurement results/calculations and analysis, it can be seen that the company's PCE value is 14.93%, the company's DPMO value is 3.477 with a sigma level of 4.20. Through the Pareto diagram, 3 main wastes were identified, namely defects at 23.08%, waiting at 23.05%, inventory at 17.28%. This shows the need for improvement efforts to increase productivity and production efficiency of product X in Pharmaceutical Companies. After carrying out the analysis, suggestions for improvements are given according to the problems that occur, such as creating OPL, checksheets, SMED, and so on. After implementation, it was found that the PCE value had increased to 19.59%, the DPMO value had decreased to 3,341, and the sigma level value had increased to 4.21 sigma.